2003
DOI: 10.1097/00000542-200301000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Laryngoscopic Intubation

Abstract: This study determined that traditional LEI teaching for nonanesthesia personnel using manikin alone is inadequate. A reevaluation of current standards in LEI teaching for nonanesthesia is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(62 citation statements)
references
References 7 publications
2
53
1
2
Order By: Relevance
“…Several investigators have reported that the mean success rate for the first 10 intubations via direct laryngoscopy by medical personnel untrained in tracheal intubation is about 35–65% and that an average of 47 attempts are needed to achieve a 90% success rate of intubation [2]. A more recent study showed a success rate of 20.6% for medical students [8], which was lower than the result of our study (Macintosh group 66.7%).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Several investigators have reported that the mean success rate for the first 10 intubations via direct laryngoscopy by medical personnel untrained in tracheal intubation is about 35–65% and that an average of 47 attempts are needed to achieve a 90% success rate of intubation [2]. A more recent study showed a success rate of 20.6% for medical students [8], which was lower than the result of our study (Macintosh group 66.7%).…”
Section: Discussioncontrasting
confidence: 82%
“…Macintosh laryngoscope is the most widely used device to facilitate tracheal intubation [1], but is considered difficult to apply for novice personnel. It was reported that a 90% success rate requires 47 times of intubation practice [2]. Actually tracheal intubation could be divided into two main steps, glottis exposure and tube insertion.…”
Section: Introductionmentioning
confidence: 99%
“…However Wang and Yealy28 suggested that paramedics required 15–20 intubations to achieve a predicted 90% success rate. Mulcaster et al 29 suggested that an 80% probability of performing a ‘good’ intubation occurred after 35 attempts in a group of medical students, respiratory therapists and paramedics. The term ‘good’ referred to technique rather than successful intubation.…”
Section: Discussionmentioning
confidence: 99%
“…The 'average' emergency medical service paramedic in the UK will see under five [19] out-of-hospital cardiac arrests a year, and in some regions far fewer than this. It is not surprising, therefore, that there is a significant complication rate associated with paramedic delivered pre-hospital intubation [10,11].…”
Section: Who Should Perform Endotracheal Intubation?mentioning
confidence: 99%